Dynamics of a double-head streamer in air: numerical analysis for an inter-electrode gap of 0.3 cm - Zablodskyi, M.; Kovalchuk, O. (Energy and Automation, 2025)
The work investigates the dynamics of a double-headed streamer discharge in air at 14 kV using hydrodynamic modeling. Numerical simulations in COMSOL Multiphysics (2D axisymmetric geometry, finite element method) revealed significant differences in the development of positive and negative streamers in a 0.3 cm gap: the negative streamer shows high initial velocity (0.4 cm/ns) that rapidly decreases, limiting its maximum propagation distance (0.15 cm), while the positive streamer accelerates over time (up to 0.0378 cm/ns), covering a greater distance (0.14 cm) due to higher electron density (up to 3.34×10²⁰ 1/m³) and more intense electric field (375×10⁵ V/m vs 119×10⁵ V/m for the negative one). The obtained results confirm the model’s ability to accurately reproduce spatiotemporal evolution of streamers, which is crucial for high-voltage device development and breakdown analysis. The study was conducted at 760 Torr with a time step of 0.05 ns over 3.75 ns. Key words: double-headed streamer, streamer discharge, numerical simulation, air gap, interelectrode gap, COMSOL Multiphysics, hydrodynamic model, positive streamer, negative streamer, air breakdown, high-voltage discharge